2015
DOI: 10.1074/jbc.m115.686865
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive Oxygen Species (ROS) Mediate p300-dependent STAT1 Protein Interaction with Peroxisome Proliferator-activated Receptor (PPAR)-γ in CD36 Protein Expression and Foam Cell Formation

Abstract: Background: CD36 plays a role in lipid uptake, foam cell formation, and atherogenesis. Results: 15(S)-HETE induces CD36 expression and foam cell formation by triggering p300-mediated STAT1 acetylation and its interaction with PPAR␥. Conclusion: STAT1 and PPAR␥ interact with each other in CD36 expression and foam cell formation. Significance: 15(S)-HETE appears to play an important role in foam cell formation, a critical event in atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Previously, we have reported that ROS are involved in the activation of Syk and Pyk2 in 15(S)-HETE-induced p300 tyrosine phosphorylation, STAT1 acetylation and its interaction with PPARγ in CD36 expression, oxLDL uptake and foam cell formation [27]. Therefore, we tested the role of ROS in CC-induced BTK activation, p300 tyrosine phosphorylation, STAT1 acetylation and its interaction with PPARγ in CD36 expression, oxLDL uptake and foam cell formation.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previously, we have reported that ROS are involved in the activation of Syk and Pyk2 in 15(S)-HETE-induced p300 tyrosine phosphorylation, STAT1 acetylation and its interaction with PPARγ in CD36 expression, oxLDL uptake and foam cell formation [27]. Therefore, we tested the role of ROS in CC-induced BTK activation, p300 tyrosine phosphorylation, STAT1 acetylation and its interaction with PPARγ in CD36 expression, oxLDL uptake and foam cell formation.…”
Section: Resultsmentioning
confidence: 94%
“…We have previously shown that STAT1, PPARγ and p300 bind to a STAT-binding site in CD36 promoter and enhance its activity in response to a lipid hydroperoxide, 15(S)-HETE [27]. In lieu of these observations, we asked the question whether these transcriptional factors and coactivator have any role in CC-induced CD36 promoter activity.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations